Education for All : Building the Schools - Theunynck, Serge (World Bank, Washington, DC, 2012)
Putting all children worldwide in school by 2015 will constitute, collectively, the biggest building project the world has ever seen. Some 10 million new classrooms will be spread over 100 countries. At current costs of about $7000 per classroom in Africa, $8000 per classroom in Latin America, and $4000 per classroom in Asia, the total price tag for construction will come to about $72 billion dollars through 2015, or about $6 billion annually. In the 1960s, most World Bank education projects focused on construction and were managed by architects. Over time, this "hardware" approach evolved into a "software" approach, with a much greater focus on teaching and learning issues. Most projects are now managed by education specialists, but construction still represents the single largest share of World Bank lending to education (45 percent of education lending).